BASIC ASSUMPTIONS OF FEMINIST CRIMINOLOGY IN THE RESULTS OF THE IMPLEMENTATION OF LAW ON PREVENTION OF FAMILY VIOLENCE - Samardžić, Stefan; Ristivojević, Branislav (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
First two years of implementation of the Law on prevention of family violence is a just an occasion to try to bring together results of its effects. Starting point for this analysis was presumption that the radical feminism and its counterpart in criminology, radical school of feminist criminology, shaped the Law. According to it family violence is a product of alleged male wish to control female sexuality. This control is conducted through social institutions such as family and marriage. As long as these institutions persist violence is repeated. Consequently, recidivism must be present as a rule. So, these institutions are to be destroyed. Some other personal factors of criminal behaviour within family do not exist. Other forms of family violence are not acknowledged and distinction between them is not made. At the beginning author gives detailed description of a numerous methodological obstacles which hamper analyses. In the next part basic presumptions originating from radical school of feminist criminology was summarily proved by brief analysis of a several provisions of the Law itself. In the third part author summarize effects of a Law by using 9 individual surveys of practice of a 9 different police departments in Republic of Serbia. Despite serious methodological obstacles and relatively scarcity of a survey sample, author`s assessment of a practice shows that basic presumptions of the radical school of feminist criminology are not proved in context of a Serbian society. If this presumption were, proven violence between partners must have been dominant in comparison with violence between relatives in analysis. In reality, violence between relatives exists in almost one-half of all cases: 43%. Furthermore, a division between three possible partner relations, a marriage, extramarital relations and a simple romance (and then on existing ones and former) shows that more formal and more stable type of relations are more represented in analysis: 51% of all cases happened in existing marriages, further 19% in existing extramarital relations and 8% in existing romances. Likewise, all existing relations are more represented in analysis in relation to former ones: 20% of cases happened in former marriages and former extramarital relations and a simple romance are represented in analysis with only 1% of all cases respectively. It is quite possible that people, educated and raised in Serbian culture, are more violent in relations in which they “invested” more. Their “investment” is a spiritual and material energy spent in relation. Those who want to have kids, raise family and acquire property and the other way round choose more formal and stabile types of relations. When faced with deprivation of these investments (kids and property) or when these are endangered, it is quite possible for people to become violent. In relations that are temporary, ephemeral or lightly perceived there is no such a kind of “investment”, and, it seems, no violence. Other possible personal factors of violent criminality are present in analysis. Perpetrators of violence are in 37% of cases unemployed. On the other hand, only 18% of them are repeated offenders, so recidivism is not high. When it comes to so called “urgent measures” as a specific type of sanctions for family violence they are issued in 2/3 of all cases. Restrain of approach and communication with victim is more frequent in comparison with eviction from home. This is understandable. With so broad definition of a member of a family, Law offers protection to persons who are in such a type of relations in which joint living is not an option. Therefore, there is not a joint accommodation from which a perpetrator should be evicted. The same applies for all former relationships, which also enjoy protections of the Law although former partners, by definition, do not live jointly any more. Ratio between measures is 35% eviction orders to 65% restrain orders. In all cases where eviction order is issued, the other measure is also issued. Out of these two facts it is possible to draw conclusion that eviction order is only measure necessary in Serbia. In Serbian culture, the notion family comprises only of relationships in which people share „table, bad and roof“. Author argues that only this type of a relation is a family, which, as a case may be, needs protection. This is one proof more that radical school of feminist criminology shaped the Law. Its teaching tries to force all relations between man and a woman, existing and former, within the notion of a family. However, concludes the author, results of implementations of the Law in Serbia speaks, on the contrary, that such a teaching is a strange body in Serbian culture, society and, consequently, legal practice.